Hubungan Pelatihan Program Posyandu Siklus Hidup Dengan Kinerja Kader Desa Di Wilayah Kerja Uptd Puskesmas Pupuan I - Riska Purnama Sari, Ni Putu; Yuliastuti, Ni Luh Sari; Mutiarahati, Ni Luh Ayu Citra (Jurnal Kesehatan, 2025)
The Posyandu Life Cycle Training Program is a human resource development program for cadres that encompasses community health services across all stages of life, from infancy to old age. However, in its implementation, the Puskesmas have several challenges as the program is still in its early stages, and training for village cadres has only been conducted in two villages. These challenges include limited knowledge and understanding of the cadres, as well as a lack of skills and communication. This research aims to determine the relationship between the Posyandu Life Cycle Training Program and the performance of village cadres within the working area of UPTD Puskesmas Pupuan I. This research uses a quantitative method with a cross-sectional approach, involving 185 respondents selected through simple random sampling. Data were collected using a questionnaire covering respondent characteristics, participation in training, and cadre performance. The chi-square test results showed a significant relationship between training and the performance quantity of village cadres in the UPTD Puskesmas Pupuan I area (p = 0.000). In addition, length of service was also significantly associated with performance quantity (p = 0.013). Observations also indicated that, overall the Posyandu in the UPTD Puskesmas Pupuan I area had implemented the Life Cycle Posyandu program. However, out of the seven Posyandu observed, only two were found to have implemented the Life Cycle Posyandu properly. This was evident from the activeness of the cadres and the participation of Posyandu attendees across all life stages, including pregnant women, infants, toddlers, adolescents, and the elderly. It is expected that the Puskesmas can provide regular training and refreshment sessions for the Posyandu program, and that village cadres can become more active in Posyandu implementation while mastering the 25 essential cadre skills that are crucial for the success of the Life Cycle Posyandu program. Keywords: The Posyandu Life Cycle, Human Resource Management, Village Cadre, Training, Performance